The impact of e-service quality and customer satisfaction on customer behavior - -, M. Fahrur Sadiq; Albari, Albari (Cita Konsultindo Research Center, 2024)
The purpose of this study is to explain the positive impact of e-service quality and customer satisfaction on customer behavior in e-commerce Tokopedia & Shopee. The research approach used is a quantitative approach. The population was all Indonesian people who have used e-commerce Tokopedia and Shopee. The sample was determined using a non-probability sampling method with a convenience sampling technique. The number of samples is 280 respondents. Research data were analyzed using SmartPls 4 software with Structural Equation Model (SEM) modeling. The results of SEM analysis showed that e-service quality has a positive effect on customer satisfaction, customer trust, repurchase intention, and e-wom, customer satisfaction has a positive effect on customer trust, repurchase intention, and site revisit, customer trust has a positive effect on repurchase intention, e-wom and site revisit, repurchase intention has a positive effect on e-wom, and e-wom has a positive effect on site revisit. Keywords: e-service quality, customer satisfaction, customer trust, repurchase intention, e-wom, serta site revisit.